Pengaruh Komunikasi dan Budaya Organisasi terhadap Kinerja Karyawan : Studi Kasus pada Karyawan Matahari Departement Store Tasikmalaya - Teddy Irawan; Cece Rakhmat; Rita Tri Yusnita (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine and analyze the effect of communication and organizational culture on employee performance (a case study on employees of Matahari Department Store Tasikmalaya). The method used in this research is causality through a case study approach. With a research sample of 135 employees of the Matahari Department Store Tasikmalaya. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that Communication has a very good assessment classification, Organizational Culture has a very good assessment classification, while Employee Performance has a good classification at Matahari Department Store Tasikmalaya Employees. Together, Communication and Organizational Culture have a significant influence on Employee Performance at Matahari Department Store Tasikmalaya Employees. Partially, communication has a significant effect on employee performance at Matahari Department Store Tasikmalaya employees. Partially, organizational culture has a significant effect on employee performance at Matahari Department Store Tasikmalaya employees